Systematic review of teacher well-being research during the COVID-19 pandemic - Aziku, Millicent; Zhang, Baohui (Frontiers in Psychology, 2024)
Introduction The COVID-19 period posed great challenges to global education systems, especially teachers even after lock-down. Teachers' wellbeing has been a concern because they have to balance health with work. Since the role of teachers is pivotal in education, there is increased in research on their wellbeing status. Method The current systematic review aims to analyze the distribution of research on teacher wellbeing from 2020 to mid-February 2024 using a quantitative method. It focuses on yearly distribution of studies, the research methods adopted by scholars, and the group of teachers investigated over the period. The PRISMA guidelines were followed, and 103 empirical studies were selected for the analysis. Results The review shows notable increase in research, particularly in 2022 and 2023, representing 37.9% and 35.9% of studies, respectively. This suggests a growing interest in teacher wellbeing among educational researchers. The findings also indicate that researchers mostly adopted quantitative methods in form of surveys (79.6%) for studies on teacher wellbeing. However, there has been an increase in qualitative and mixed-methods research recently, with qualitative research accounting for 9.7% and mixed-method research accounting for 10.7%. The review also identified a greater focus on teachers in general than on specific group of teachers.